آثار التعمير البشري بمنطقة الأوراس: مسح وادي الطاقة دراسة حالة - حسين، محمد الشريف Hussein, Mohammed Alsherif (جامعة أبوبكر بلقايد تلمسان - مخبر التراث الأثري وتثمينه, 2016)
عمر الإنسان منطقة الأوراس منذ فترة ما قبل التاريخ السحيقة، كما يمكن أن يستنبط من كثرة البقايا الأثرية، الشاملة لمختلف فترات التاريخ القديم (فترة ما قبل التاريخ، فترة فجر التاريخ، وفترة الحضارات القديمة) ولاسيما منها السفوح الشمالية لكتلة جبال الأوراس المنيعة، منطقة "وادي الطاقة" محل هذه الدراسة، وما ينطوي عليه من آثار في غاية الأهمية، حيث ماتزال جد مغمورة في غياب التنقيبات الأثرية، والدراسات التاريخية الخاصة بها حتى الآن؛ إذ تهدف الدراسة إلى إبراز الأهمية العلمية لهذه المنطقة المنسية في انتظار القيام بأبحاث اثريه أعمق مستقبلا.
Since the prehistoric period the area of Aures was inhabited by human, that is what has been proved by the archaeological remains of various historic periods Particularly; the northern side of the Aures montains (TAGA valley). where there are many different archaeological sites, that belongs to different periods. whom shows human occupation in this area (prehistoric, Proto history, Antiquity) in the same time we can see the spatial distribution of these archaeological sites. And most of it was unknown because of the archaeological research absence, the purpose of this study is to show scientific importance of this Area.
Keywords: المواقع الأثرية -- التراث المعماري -- التاريخ القديم -- الجزائر